(untitled) (Contemporary Journal of Social Science Review, 2026)
The present phenomenological research explored the potential of artificial intelligence to revolutionize teacher education in Pakistan. As a sustainable approach to preparing future AI-ready schools, this study explored the perceptions of teachers, educators, and AI experts. To understand perceptions and experiences related to AI in teacher education, the data were collected from 12 participants. The participants were selected purposively with professional links to teacher education and educational technology. Interviews were used to collect data. This was then analysed using thematic analysis to identify the meanings, concerns, and expectations of the participants regarding AI integration into teacher education. Three important themes were identified. AI as a transformative force for teaching and learning, Ethical AI literacy, teacher professional decision-making, and AI-driven sustainable teacher education. The results revealed to us that AI should support rather than replace teachers’ professional judgment. The study also highlighted ethical concerns related to data privacy, algorithmic bias, academic integrity, misinformation, and overdependence on AI-generated content in the curriculum. The participants viewed AI as a potential means to promote inclusive and sustainable education. Particularly through differentiated learning materials, multilingual support, and support for diverse learners, AI can be helpful for future sustainable schools. They cautioned that unequal access to digital resources may widen educational disparities. If they did not address this through policy and institutional support, we may be left behind the progressive world in this regard. The study concludes that AI-powered teacher education in Pakistan requires a balanced framework based on pedagogical innovation. Moreover, it includes ethical responsibility, teacher agency, and sustainable inclusion.